Encouraging Dispute Resolution in the Election Process through Non-Litigation Mechanism - Rahmadi, Raden Yoseph Gembong; Firdaus, Mohamad; Hidayat, Arief (JOELS: Journal of Election and Leadership, 2024)
The article discusses the mainstreaming of mediation as a mechanism in the dispute resolution process in elections in Indonesia. In various elections or elections, it is reflected that this mediation mechanism is minimally used as an instrument in resolving disputes in the election process. In fact, theoretically, this mediation process has many advantages compared to the litigation process. The number of disputes in the election process that prioritize the litigation process reflects the low interest or trust of participants, as well as the lack of maximum Election Supervisors who are positioned as referees to maximize this role and function properly. It was recorded that from the 2014 election to 2024, there were 789 dispute complaints filed by election participants. This article uses normative juridical law research methods that are used using primary, secondary and tertiary legal literature and materials. The results of the discussion show that Bawaslu as an institution attributed by law to resolve election disputes in the majority is still taking the path of litigation. It is understandable that mediation has been carried out but has failed to be carried out. However, this condition must again be encouraged by the spirit of mediation to reach a consensus so that election disputes can be channelized not only through adjudication.